5‐HT3A receptors maintain hippocampal LTP in a CB1 and GABAA receptor‐ dependent manner for spatial memory. (14th February 2022) - Yu, Yan; Li, Jing‐Jing; He, Xiao‐Qian; Lai, Zi‐Ying; Hao, Rui; Qi, Yu; Cao, Dong‐Qing; Fu, Ming; Ma, Hong; Xie, Qiu‐Chen; Sun, Mu; Huang, Zhi‐Li; et al.
Abstract : Background and Purpose: As the only ionotropic receptor in the 5‐HT receptor family, the 5‐HT3 receptor (5‐HT3 R) is involved in psychiatric disorders and its modulators have potential therapeutic effects for cognitive impairment in these disorders. However, it remains unclear how 5‐HT3 Rs shape synaptic plasticity for memory function. Experimental Approach: Extracellular as well as whole‐cell electrophysiological recordings were used to monitor hippocampal LTP and synaptic transmission in hippocampal slices in 5‐HT3 AR knockout or 5‐HT3 AR‐GFP mice. Immunocytochemistry, qRT‐PCR and western blotting were used to measure receptor expression. We also assessed hippocampal dependent cognition and memory, using the Morris water maze (MWM) and novel object recognition. Key Results: We found that 5‐HT3 R dysfunction impaired hippocampal LTP in Schaffer collateral (SC)‐CA1 pathway in hippocampal slices, by facilitating GABAergic inputs in pyramidal cells. This effect was dependent on 5‐HT3 Rs on axon terminals. It resulted from reduced expression and function of the cannabinoid receptor 1 (CB1 R) co‐localized with 5‐HT3 Rs on axon terminals, and then led to diminishment of tonic inhibition of GABA release by CB1 Rs. Inhibition of CB1 Rs mimicked the facilitation of GABAergic transmission by 5‐HT3 R disruption. Consequently, mice with hippocampal 5‐HT3 R disruption exhibited impaired spatial memory in MWM tasks. Conclusion and Implications: These results suggest that 5‐HT3 Rs are crucial in enabling hippocampal synaptic plasticity via a novel CB1 R‐GABAA ‐dependent pathway to regulate spatial memory.